Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Help please I'll mark you as brainlist if the answer is correct

if (x + q) is a factor of two polynomials x2 + px + q and x2 + mx + n, then prove that a = n-q m-p​


Sagot :

If (x + q) is factor of two polynomial [tex]x^2+px+q[/tex] and [tex]x^2+mx+n[/tex] than [tex]a = \frac{n - q}{m- p}[/tex].

x + a is factor of equations  [tex]x^2+px+q[/tex] and [tex]x^2+mx+n[/tex]

What is a polynomial equation?

Polynomial equation is equation of independent variables.


Putting it in both the equations

[tex]x^2+px+q=0[/tex]                          
[tex](-a)^2+p(-a)+q=0\\a^2-ap+q=0 ........(1)[/tex]  

[tex]x^2+mx=n = 0\\(-a)^2+m(-a)+n=0\\a^2-am+n=0 .....(2)[/tex]

subtracting (2) from (1)

[tex]-am+ap+n-q=0[/tex]
[tex]a=\frac{n-q}{m-p}[/tex]

Thus, the required expression is [tex]a=\frac{n-q}{m-p}[/tex].

learn more about polynomial here:
https://brainly.com/question/11536910

#SPJ1



We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.